Reference Ability Neural Network‐selective functional connectivity across the lifespan. Issue 3 (27th October 2020) - Argiris, Georgette; Stern, Yaakov; Habeck, Christian
Abstract: Previous studies have demonstrated that four latent variables, or reference abilities (RAs), can account for the majority of age‐related changes in cognition: these being episodic memory, fluid reasoning, speed of processing, and vocabulary. In the current study, we focused on RA‐selective functional connectivity patterns that vary with both age and behavior. We analyzed fMRI data from 287 community‐dwelling adults (20–80 years) on a battery of tests relating to the four RAs (three tests per RA = 12 tests). Functional connectivity values were calculated between a pre‐defined set of 264 ROIs (nodes). Across all participants, we (a) identified connections (edges) that correlated with an RA‐specific indicator variable and, indexing only these edges; (b) performed linear regression analysis per edge, regressing indicator correlations (Model 1) and connectivity values (Model 2) on Age, Behavioral Performance, and the Interaction term; and (c) took the conjunction of significant edges between models. Results revealed a different subset of edges for each RA whose connectivity strength and domain‐selectivity varied with age and behavior. Strikingly, the fluid reasoning RA was particularly vulnerable to the effects of age and displayed the most extensive connectivity and selectivity "footprint" for behavior. These findings indicate that different functional networks are recruited across RA, with fluid reasoning displaying a special status among them. Abstract : In the current study, we focused on RA‐selective functional connectivity patterns that vary with both age and behavior. Analyzing fMRI data from 287 community‐dwelling adults (20–80 years) on a battery of tests relating to the four RA (three tests per RA= 12 tests), we demonstrated that different subsets of edges for each RA displayed connectivity strength and domain‐selectivity that varied with age and behavior; moreover, the fluid reasoning RA was particularly vulnerable to the effects of age and displayed the most extensive connectivity and selectivity "footprint" for behavior. These findings indicate that different functional networks are recruited across RA, with fluid reasoning displaying a special status among them.